Secure Data Storage Scheme using Blockchain for Federated cloud - Munwar, Shaik; Ramani, K; Madhavi, K (International Journal of Computer Sciences and Engineering, 2025)
With the Internet technology development, the volume of data is growing immensely. To deal with huge volume of data, cloud storage has gained great attention from organizations and businesses because of its easy and efficient to adoption procedure. Traditional cloud storage has come to rely almost exclusively on large storage providers acting as trusted third parties to transfer and store data. Though, cloud Provider offers considerable security features, with increasing demands and usage, these centralized systems have become major targets for hacks and data breaches. This makes the data vulnerable and prone to tampering. In this paper, to address the above problems and proposed a distributed blockchain-based security scheme for storage in federated cloud, where users can divide their own files into fragments, encrypted those data fragments, and upload those encrypted fragments randomly into the federated clouds